Peran Internet dalam Meningkatkan Pembangunan Demokrasi di Kawasan Barat Indonesia [The Role of the Internet in Improving Democratic Development in Western Indonesia - Dyah Makutaning Dewi; Dewi Widyawati (Sekretariat Jenderal DPR RI, 2021)
Guaranteed freedom of the press has become an absolute requirement for democratization in Indonesia. Following the 1998 Reform in Indonesia, the press is no longer under the pressure and control of the state. The Indonesia Democracy Index is an index that describes the dynamics of democracy in Indonesia. The developing democratization is further supported by massive development in technology and information. In describing the level of development of information and communication technology, an index is used as a standard measure for information and communication technology development in an area called the Information and Communication Technology Development Index. Of the 11 indicators that make up the index, the fastest growing indicator is the percentage of households with internet access. The availability of internet as a medium of information and communication has encouraged the public to voice their aspirations through different online platforms. The research employs multiple linear regression method. The data used is sourced from Statistics Indonesia and cover 17 provinces in the Western Region of Indonesia. The results showed that the percentage of households accessing the internet and the percentage of poor people had a positive and significant effect on the Indonesian Democracy Index in western Indonesia. Supported by efforts such as improving the development of infrastructure, training, and other measures, it would be on the government’s best interest to work with different parties to support and increase the number of internet users. Moreover, more public education on the importance of democracy is also necessary to ensure higher public participation in democracy.AbstrakJaminan terhadap kebebasan pers telah menjadi syarat mutlak bagi upaya demokratisasi di Indonesia. Setelah terjadinya reformasi di Indonesia pada tahun 1998, tidak terjadi lagi tekanan dan pengendalian oleh negara terhadap pers. Indeks Demokrasi Indonesia merupakan suatu indeks yang menggambarkan dinamika demokrasi di wilayah Indonesia. Demokratisasi yang semakin berkembang ini didukung dengan perkembangan teknologi dan informasi yang masif. Dalam menggambarkan tingkat pembangunan teknologi informasi dan komunikasi, terdapat suatu indeks sebagai ukuran standar pembangunan Teknologi Informasi dan Komunikasi di suatu wilayah yang dinamakan Indeks Pembangunan Teknologi Informasi dan Komunikasi. Dari 11 indikator penyusun indeks tersebut, indikator yang berkembang pesat yaitu persentase rumah tangga yang memiliki akses internet. Adanya internet yang merupakan media informasi dan komunikasi, mendorong masyarakat untuk menyuarakan aspirasinya melalui media internet. Metode penelitian yang digunakan di dalam penelitian ini menggunakan metode regresi linear berganda. Data yang digunakan bersumber dari Badan Pusat Statistik meliputi 17 provinsi di Kawasan Barat Indonesia. Hasil penelitian menunjukkan persentase rumah tangga yang mengakses internet dan persentase penduduk miskin berpengaruh positif dan signifikan terhadap Indeks Demokrasi Indonesia di Kawasan Barat Indonesia. Melalui berbagai langkah seperti meningkatkan pembangunan infrastruktur, pelatihan, dan sebagainya, sebaiknya pemerintah bekerja sama dengan beberapa pihak untuk mendukung dan meningkatkan pengguna internet. Selain itu, perlu dilakukan sosialisasi mengenai demokrasi sehingga masyarakat turut aktif dalam berdemokrasi di negeri ini.